A subpopulation of high IL-21-producing CD4+ T cells in Peyer’s Patches is induced by the microbiota and regulates germinal centers - Jones, Leigh (2018)
The production of IL-21 by T follicular helper (Tfh) cells is vital in driving the germinal centre reaction and high affinity antibody formation. However, the degree of Tfh cell heterogeneity and function is not fully understood. We used a novel IL-21eGFP reporter mouse strain to analyze the diversity and role of Tfh cells. Through the analysis of GFP expression in lymphoid organs of IL-21eGFP mice, we identified a subpopulation of GFP+, high IL-21 producing Tfh cells present only in Peyer’s Patches. GFP+Tfh cells were found to be polyclonal and related to GFP−Tfh cells of Peyer’s Patches in TCR repertoire composition and overall gene expression. Studies on the mechanisms of induction of GFP+Tfh cells demonstrated that they required the intestinal microbiota and a diverse repertoire of CD4+ T cells and B cells. Importantly, ablation of GFP+ cells resulted in a reduced frequency of Peyer’s Patches IgG1 and germinal center B cells in addition to small but significant shifts in gut microbiome composition. Our work highlights the diversity among IL-21 producing CD4+ Tfh cells, and the interrelationship between the intestinal bacteria and Tfh cell responses in the gut.